Health evaluation of employees occupationally exposed to methylene chloride: clinical laboratory evaluation - Ott, M Gerald; Skory, Lyman K; Holder, BB; Bronson, Julie M; Williams, Paul R (Scandinavian Journal of Work, Environment & Health, 1983)
Hematopoietic effects seen in heavy cigarette smokers have been attributed to the carbon monoxide present in smoke. Since methylene chloride is partially metabolized in vivo to form carboxyhemoglobin, the pattern of hematologic changes relative to both the methylene chloride exposure and the cigarette smoking status of employees in two fiber production plants was investigated. Six serum constituents, changes in which could indicate liver injury, were also examined in relation to methylene chloride exposure. The observed increase in red cell counts, hemoglobin, and hematocrit among the women but not among the men exposed to about 475 ppm of methylene chloride was suggestive of a compensatory hematopoietic effect. Similar changes have been observed in cigarette smokers, but not necessarily only in women. Another frequently reported change in the hematology of smokers, increased mean corpuscular volume, was not seen with methylene chloride exposure. These findings suggest that some, but not all, of the hematologic changes observed in cigarette smokers may be explained on the basis of carbon monoxide alone. A dose-related increase in serum bilirubin was observed for both the men and the women exposed to methylene chloride. This appears to be an isolated finding, as no corresponding pattern of dose-related changes consistent with either liver injury or hemolysis was observed for other serum and blood constituents.
Keywords: carboxyhemoglobin; clinical laboratory evaluation; employee; health evaluation; hematopoietic effect; laboratory evaluation; methylene chloride; occupational exposure; smoking